Dimensions of Occupational Stress Impacting Turnover Intentions Amongst BPO Employees : An Empirical Study - Rai, Rashmi; Tripathi, Shruti (Prabandhan: Indian Journal of Management, 2017)
Nowadays, many organizations are confronted with the problem of higher level of employee turnover that brings higher replacement costs to these companies. Especially analysing the current situation in the BPO Industry, it is observed that the turnover intention of call centre employees is greater than its expected level and has become a major threat to their existence. Job stress is one of the major factors which tremendously influences this problem. This study mostly focused upon the impact of job stress (JS) on employee turnover intention (TI) of call centre employees in the BPO industry. Eight five respondents participated in the study. The study was carried out using the survey method. For the survey, the standardized questionnaire of Osipow (1998) for occupational stress and Rajkumar and Karthik Sridar (2015) for turnover intentions were used. The results revealed that scope of occupational stress, that is, role uncertainty/ambiguity, role boundary, role responsibility, and the physical environment had a substantial significant impact on turnover intentions of employees. The dimensions of occupational stress, that is, role insufficiency and role overload had a slight impact on turnover intentions of employees. The regression model stated that there was dependency between occupational stress and turnover intentions. The study suggested that empowerment should be provided at the workplace so that the employees can minimize their inter role distance and can increase job involvement. To make a productive workforce, the sub - variablesÂ of job stress like role stagnation, role isolation, and role overload should also be minimized by working more on the person-organization-fit at the time of recruitment and selection.